Acetone Extract of Turmeric (CURCUMA LONGA) Attenuates Inflammation, Dyslipidemia, and Hepatorenal Dysfunction in Streptozotocin-Induced Type 2 Diabetic Rats - Bako, Hauwa'u Yakubu; Irene, Agboola Omolara; Ladan, Bilkisu Mohammed; Mohammed, Zainab Kasim; Auta, Richard (FUDMA Journal of Sciences, 2026)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder associated with hyperglycemia, inflammation, dyslipidemia, and organ dysfunction. This study investigated the anti-inflammatory, hypolipidemic, and hepatorenal protective effects of acetone extract of Turmeric in streptozotocin-induced type 2 diabetic rats. Thirty male Wistar rats were randomly assigned into five groups (n = 6): normal control, diabetic control, turmeric-treated groups (100 and 200 mg/kg body weight), and metformin-treated group (500 mg/kg). Type 2 diabetes was induced using 10% fructose administration for 14 days followed by a single intraperitoneal injection of streptozotocin (50 mg/kg). Biochemical analyses were performed to evaluate inflammatory markers (TNF-α and IL-6), glucose tolerance, lipid profile, and liver and kidney function parameters. Data obtained were analyzed using multivariate analysis of variance (MANOVA) and results were considered significant at P < 0.05. Diabetic control rats showed significant elevations in fasting blood glucose, TNF-α, IL-6, total cholesterol, triglycerides, LDL-C, ALT, AST, ALP, urea, and creatinine levels, with a concomitant reduction in HDL-C and glucose clearance ability compared to the normal control group. Treatment with turmeric extract significantly ameliorated these alterations. The 100 mg/kg dose produced greater improvement in lipid profile and reduction in atherogenic indices, while the 200 mg/kg dose demonstrated stronger hepatoprotective effects through greater reductions in liver enzyme activities. These findings suggest that acetone extract of Turmeric possesses anti-inflammatory, hypoglycemic, hypolipidemic, and hepatorenal protective properties, supporting its potential as a complementary therapeutic agent in the management of T2DM and its associated complications.
Keywords: Type 2 Diabetes Mellitus; Turmeric; Inflammation; Dyslipidemia; Hepatorenal Dysfunction; Insulin Resistance